Evaluation the Pollution of Sediments of the Shatt Al-Hillah with Heavy Metals by Using the Pollution Indices (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The level of pollutant of heavy metals (Hg, Co,  Pb V, Cr, Ni, Sr, Zr, Mo, Cu, Rb,  Zn, As,Th, U) , in the sediment samples on the banks of the Shatt al-Hillah River The study was conducted in the Department of Earth Science at the collge  of Science, University of Babylon, 14 samples of sediments  ware collected from the banks of the river of Shatt Al-Hillah. The average concentration of the heavy metal  in the sediment of the river bank  in descending order: Sr (360.6 ppm) ,Cr (285.9 ppm ), Ni (203.2 ppm), Co (169.9 ppm), Zr (166.3 ppm),. V (116.4ppm) , Zn (91.6 ppm), Cu (48.8 ppm ), Rb (41.9 ppm ), Pb (18.1 ppm), As(11.1 ppm), Hg(5.7ppm),Th (4.2 ppm),Mo(3.7 ppm), U(2ppm,. The geoaccumulation index (Igeo) for Hg